The Productive Impulse of Management of Organizations. Kind Leadership. - Kalantaryan, Edgar (YSU Journal of International Affairs, 2024)
Team leaders at leading organizations are beginning to rebuild their skills with a training methodology that can deliver unprecedented progress for any organization. When a leader emphasizes listening, recognition, communication and talent appreciation, in this case we are dealing with Kind Leadership. A new approach that develops people’s professional skills, helping them to use their own potential by creating the right space and opportunity. In a corporate environment, it allows you to create a positive and stimulating environment where employees feel valued and important. Employees with a well-mannered leader feel more confident because they feel they can express their thoughts and concerns without being judged. Goodness increases communication and cooperation, a good leader listens carefully and respects the ideas of others. This method of leadership includes qualities such as good education, politeness, management skills, benevolence, etc.. It is also important to note that in the management of organizations, kindness is not equivalent to weakness, weakness, passion, moreover, its strength is to balance power and compassion, facing conflicts with understanding.